Análise das propriedades do PP injetado em molde-protótipo em Zamac-8 visando a obtenção de protótipos funcionais - Junkes, Vanderlei (2014)
The use of prototype tooling is an option to obtain functional prototype of injection molded plastic parts. These prototypes should have mechanical and physical characteristics as close as possible to the final parts obtained in production molds. In order to reduce manufacturing cost and time of these molds, alternative materials, such as aluminum and zinc alloys, can be employed. The difference in thermal conductivity of these materials results in a variation of the cooling rates, which can influence the mechanical properties of the moldings. The main objective of this work is to understand the influence of the prototype tooling material (zamak-8) and also the variation of mold temperature (TMold) and the melt temperature (TMelt) on the mechanical properties of Polypropylene (PP). The idea is then to verify if these temperature parameters may allow obtaining functional prototypes with similar characteristics to the PP injected in a steel mold. The influence of the zamak-8 material and the TMold and TMelt on the properties of the molding was studied by comparison with the molding injected in a steel mold. The characterization techniques used were tensile and impact tests and differential scanning calorimetry (DSC). The results showed that the prototype tooling using zamak-8 has a significant influence only in the impact energy. By varying the TMold and TMelt, moldings injected in the prototype tooling with zamak-8 were obtained with different properties, confirming the influence of these parameters on the molding. In this way, a regression model was developed where, by optimizing these temperatures, it is possible to predict a result. Thus, in this study it was possible to reduce the influence of the zamak-8 on the molded, and regression was shown to be an important tool in the search for functional prototypes closer mechanical properties of the final product.